2015
DOI: 10.1111/pin.12257
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent and up‐regulated vimentin expression in micropapillary components of lung adenocarcinomas and its adverse prognostic significance

Abstract: The factors conferring the increased malignancy on lung adenocarcinoma with micropapillary component (AC-MPC) remain to be elucidated. On proteomics based on 2-dimensional gel electrophoresis, 19 proteins differentially expressed by more than 1.5-fold between AC-MPC and conventional adenocarcinoma (CAC); in particular, vimentin, one of the proteins, was 3.5-fold up-regulated in AC-MPC. Subsequent semi-quantitative investigation by immunohistochemistry with large cohorts comprised 101 AC-MPC and 119 CAC, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“… 48 , 49 In recent studies, vimentin has been found to have higher expression in MPPAC, and it is correlated with higher risks of vascular invasion and lymph node metastasis. 50 , 51 In a sample of 101 MPPACs and 119 conventional ADCs of stages I–III, vimentin expression was detected by semiquantitative immunohistochemistry. Of the 101 MPPACs, vimentin expression scores of MPP and background non-MPP were 4.0±2.1 and 2.3±1.9, respectively, with a P -value of <0.0001.…”
Section: Molecular Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“… 48 , 49 In recent studies, vimentin has been found to have higher expression in MPPAC, and it is correlated with higher risks of vascular invasion and lymph node metastasis. 50 , 51 In a sample of 101 MPPACs and 119 conventional ADCs of stages I–III, vimentin expression was detected by semiquantitative immunohistochemistry. Of the 101 MPPACs, vimentin expression scores of MPP and background non-MPP were 4.0±2.1 and 2.3±1.9, respectively, with a P -value of <0.0001.…”
Section: Molecular Featuresmentioning
confidence: 99%
“…High vimentin expression in MPP was an independent adverse prognostic factor for both overall survival (OS) and disease-free survival (DFS) (hazards ratio [HR] =1.71, 95% confidence interval [CI] =1.00–2.99, P =0.047). 51 …”
Section: Molecular Featuresmentioning
confidence: 99%
“…In this study, the micropapillary adenocarcinoma histological subtype showed a significantly increased rate of high‐IMMT expression compared to that with other histological subtypes. Adenocarcinoma with a micropapillary pattern is characterized by more frequent and prominent vascular invasion, a higher incidence and more advanced lymph node involvement, and a poorer prognosis compared to those with conventional papillary adenocarcinoma without the micropapillary pattern . Little is known about the factors and mechanisms underlying the more aggressive nature of this tumor subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinoma with a micropapillary pattern is characterized by more frequent and prominent vascular invasion, a higher incidence and more advanced lymph node involvement, and a poorer prognosis compared to those with conventional papillary adenocarcinoma without the micropapillary pattern. [17][18][19] Little is known about the factors and mechanisms underlying the more aggressive nature of this tumor subtype. However, IMMT might be involved in the aggressive nature of this tumor type.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most MPPAC patients are males and nonsmokers [9,12,[16][17][18][19]. Comparing with other ACs, the molecular markers of MPPAC, including vimentin, napsin A, phosphorylated c-Met, cytoplasmic maspin, Notch-1, MUC1, and tumoral CD10, are highly expressed; conversely, markers such as MUC4 and surfactant apoprotein A have low expression in MPPAC [20][21][22][23][24][25][26][27]. MPPAC has a higher frequency of epidermal growth factor receptor (EGFR) mutations and v-raf murine sarcoma viral oncogene homolog B1 (BRAF) mutations as compared to other histological subtypes [3,22,[28][29][30][31], while the kirsten rat sarcoma 2 viral oncogene homolog (KRAS) Results mutations or anaplastic lymphoma kinase (ALK) rearrangement are similar in all subtypes [22,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%